Subterranean Termites - P.G. Koehler; C.L. Tucker; T.J. Weissling (EDIS)
This document provides an overview of subterranean termites, detailing their biology, life cycle, and the damage they cause. It explains the different castes within a termite colony, including workers, soldiers, and reproductives. The document emphasizes the importance of detecting infestations early through signs like mud tubes, winged reproductives, and wood damage. It also outlines various prevention and control methods, including preconstruction and postconstruction treatments, the use of termiticides, and termite baits. Proper identification and professional pest control are recommended for effective management. First Published: April 1993.